Menerima dan Memaknai Diagnosis: Pengalaman Family Caregiver dalam Proses Penyampaian Diagnosis Skizofrenia - Dewi, Elsa Fairuza; Poerwandari, Elizabeth Kristie (Psyche 165 Journal, 2023)
The diagnosis of schizophrenia is something important that needs to be informed, not only to the patient but also to the family caregiver. Delivering a clear diagnosis and related information, can help the family caregiver understand their family member's condition and their role as a family caregiver. This, in turn, can impact the success of the patient's treatment process. However, in practice, there are still many healthcare professionals who are hesitant to explicitly communicate a diagnosis of schizophrenia. In Indonesia, some family caregivers experiencing a lack of information about the diagnosis of schizophrenia provided by healthcare providers. This study aims to understand the experiences of family caregivers of individuals with schizophrenia regarding the process of diagnosis communication and other aspects related to the diagnosis of schizophrenia. Semi-structured interviews were conducted with 5 family caregivers who were aware of the diagnosis process of their family members. The data analyzed using a reflexive thematic analysis approach. The results revealed several themes in the experiences of family caregivers during the diagnosis communication process, including pre-diagnosis assumptions, uncertainty about diagnosis-related information, various responses after receiving the diagnosis, the presence of additional sources of information, communication patterns with healthcare providers, and expectations related to the diagnosis communication process. In conclusion, most family caregivers expect a clear, detailed, and comprehensive diagnosis communication. Additionally, family caregivers emphasize the importance of warmth, empathy, and a willingness to spend time discussing their family member's condition with caregivers.